2008
DOI: 10.1681/asn.2007111179
|View full text |Cite
|
Sign up to set email alerts
|

CXCL9, but not CXCL10, Promotes CXCR3-Dependent Immune-Mediated Kidney Disease

Abstract: Chemokines are instrumental in macrophage-and T cell-dependent diseases. The chemokine CCL2 promotes kidney disease in two models of immune-mediated nephritis (MRL-Fas lpr mice and the nephrotoxic serum nephritis model), but evidence suggests that multiple chemokines are involved. For identification of additional therapeutic targets for immune-mediated nephritis, chemokine ligands and receptors in CCL2Ϫ/Ϫ and wild-type (WT) MRL-Fas lpr kidneys were profiled. The focus was on intrarenal chemokine ligand/recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
82
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 52 publications
6
82
0
Order By: Relevance
“…In this study, we show for the first time that CXCR3 deficiency improves renal outcome in the MRL/lpr model of lupus nephritis, not only by reducing the number of renal Th1 cells, but also by almost completely abolishing Th17 cell infiltration. In agreement with published studies (40,41), renal mRNA expression of all three CXCR3 ligands, Mig/CXCL9, IP-10/ CXCL10, and ITAC/CXCL11, as well as CXCR3 mRNA, increased with progression of nephritis in MRL/lpr animals from 10 wk of age. At the time of sacrifice (20 wk of age), intrarenal chemokine levels of all CXCR3 ligands were slightly reduced in MRL/lpr CXCR3 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we show for the first time that CXCR3 deficiency improves renal outcome in the MRL/lpr model of lupus nephritis, not only by reducing the number of renal Th1 cells, but also by almost completely abolishing Th17 cell infiltration. In agreement with published studies (40,41), renal mRNA expression of all three CXCR3 ligands, Mig/CXCL9, IP-10/ CXCL10, and ITAC/CXCL11, as well as CXCR3 mRNA, increased with progression of nephritis in MRL/lpr animals from 10 wk of age. At the time of sacrifice (20 wk of age), intrarenal chemokine levels of all CXCR3 ligands were slightly reduced in MRL/lpr CXCR3 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 92%
“…There is still a lack of evidence to support a protective role of interference with the CXCR3 receptor-ligand axis in chronic renal autoimmune disease, such as the lupus nephritis of MRL/lpr mice. As in NTN, IP10/CXCL10 deficiency did not lead to improvement of the clinical course of glomerulonephritis in this murine model of human lupus nephritis (40). The influence of CXCR3 deficiency has not been studied to date.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…31,32 The recruitment of CXCR3 + T cells into the kidney was shown in human and experimental GN, 33,34 and subsequent studies showed that CXCR3 mediates T effector cell recruitment and tissue injury in experimental models of crescentic GN. 35,36 These studies show the potential beneficial effect of nonselective CXCR3 blockade in crescentic GN. Our results suggest, however, that specific targeting of CXCR3 on T H 1 cells or the blockade of T H 1-specific mediators would be even more effective than pan-CXCR3 neutralization in T H 1-driven inflammatory diseases.…”
Section: Discussionmentioning
confidence: 79%